2009
DOI: 10.1007/s10620-009-0813-5
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Antibody Testing, Permeability Testing, and Zonulin Levels with Small-Bowel Biopsy in Celiac Disease Patients on a Gluten-Free Diet

Abstract: Active celiac disease is associated with positive endomysial (EMA) and tissue transglutaminase (TTG) antibodies, elevated zonulin levels, and increased intestinal permeability. There is little known about what happens to these immunologic and structural abnormalities in patients on a gluten-free diet and their correlation with small-bowel biopsy changes. Adult patients previously diagnosed with celiac disease and on a gluten-free diet for greater than 1 year were considered for the study. All patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 26 publications
2
36
2
Order By: Relevance
“…Tissue levels of zonulin in the intestine were much higher in celiac patients compared to controls [21]. Higher levels of zonulin in serum correlate with higher intestinal permeability as measured with the L/M test [56,57]. This is in contrast with our study, where no abnormal L/M ratio was measured while we did find changes in zonulin levels.…”
Section: Case Seriescontrasting
confidence: 99%
“…Tissue levels of zonulin in the intestine were much higher in celiac patients compared to controls [21]. Higher levels of zonulin in serum correlate with higher intestinal permeability as measured with the L/M test [56,57]. This is in contrast with our study, where no abnormal L/M ratio was measured while we did find changes in zonulin levels.…”
Section: Case Seriescontrasting
confidence: 99%
“…In our study, CD patients with lower expression of TJP1 had higher levels of anti-gliadin as well as anti-tTG IgA antibodies, which might reflect greater intestinal permeability to gluten in these persons [22,26]. The link between enhanced gut permeability to gliadin and production of anti-gliadin IgA antibodies was already reported by Bonamico et al [47] and was confirmed by other authors [20].…”
Section: Discussionsupporting
confidence: 87%
“…Antibodies to the autoantigen tissue transglutaminase (tTG) have also been shown to increase intestinal permeability in CD [25]. Duerksen et al [26] found positive correlation of tTG antibodies with the severity of intestinal lesions and intestinal permeability. Increased permeability of the small intestinal mucosa has also been shown in patients with T1D, which is suggested to be important in the pathogenesis of T1D [27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Then, ASCA have been described in coeliac disease (CD) [4][5][6], in autoimmune hepatitis [7], in primary biliary cirrhosis [8], in Behçet's disease [9], in ankylosing spondylitis [10], and in systemic lupus erythematosus [11]. In all these diseases there is an increased intestinal permeability [12][13][14][15][16]. In addition, S. cerevisiae, an exogenous yeast, is found in foodstuffs especially in bread.…”
Section: Introductionmentioning
confidence: 99%